Napoleon - Unknown:::Creator::::::::::::; Delaroche, Paul, 1797-1856 (artist):::Contributor:::::::::::: (Johnson, Wilson & Co. Publishers; United States; New York)
Anonymous engraving of Napoleon based on a painting by Paul Delaroche, with a facsimile of Napoleon's signature.